2003
DOI: 10.1188/03.onf.e100-e105
|View full text |Cite
|
Sign up to set email alerts
|

Family Satisfaction With Perception of and Barriers to Terminal Care in Japan

Abstract: Oncology nurses need to consider different cultural backgrounds when offering specific care to patients with terminal cancer. Patients and their families must be educated about the efficacy of narcotics in the care of terminally ill patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Reasons for underreporting included fear of side effects, which they felt could shorten the patient's life and fear that the patient would become addicted (Lin et al. 2000, Ogasawara et al. 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for underreporting included fear of side effects, which they felt could shorten the patient's life and fear that the patient would become addicted (Lin et al. 2000, Ogasawara et al. 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Steinhauser et al. (2000) reported that families feared bad dying more than death and Dunne and Sullivan (2000) found that the most stressful factor experienced by relatives was poor pain control (Ogasawara et al. 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Abhorrence of death still resides in the mind of the Japanese and facilitates reluctance towards any termination of life [19]. Some participants in a survey of family members of deceased cancer patients wished for continuation of active treatments, and the authors discussed that the QOL of the patient included the continuation of such treatment as long as possible [20]. In our survey, physicians emphasized patient conditions of brain death and severe dementia (in which the QOL of the patients are thought to be objectively low) significantly more than laypeople (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…If, however, lacking nursing diagnoses and intervention related to death and dying may be related to sociocultural beliefs about death and dying, and to nurses’ negative feelings and attitudes, it would be very difficult to resolve this issue. Japanese nurses’ beliefs and attitudes may reflect the traditional Asian family‐centered decision‐making system and physicians’ paternalism (Ogasawara, Kume, & Andoh, 2003). Moreover, many patients and their families may experience emotional difficulties but not express their feelings to the medical staff.…”
Section: Discussionmentioning
confidence: 99%